(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2005)
The use of photographs to determine people’s identity has been applied since the middle of the 19th century and included in individual’s criminal and prison records1-3. With the development and establishment of fingerprint technology, fingerprints became more widely used and proved to be more reliable method of identification. However, even today, throughout the world, photographs are still used and are included as part of prisoner’s records. Law agencies universally, routinely use fingerprints and photographs for criminal records. These images commonly referred to as ‘MUG SHOTS’ are characterized by two photographs, one facing directly into the camera and the other a profile. This persistent use of photographs raises the question, as to why photographs are used so commonly when fingerprints are a more reliable source of identification? The answer is quite simple; photographs are used so that a lay person, including police or customs officials, can make cursory identification by comparing the suspect in question with his / her photographs. Fingerprint identification on the other hand, requires a trained and qualified eye viz. a finger print expert4.